Non-enzymatic posttranslational modifications of bovine serum albumin by oxo-compounds investigated by high-performance liquid chromatography-mass spectrometry and capillary zone electrophoresis-mass spectrometry - Zmatliková, Zdeňka; Sedláková, Pavla; Lacinová, Katerina; Eckhardt, Adam; Pataridis, Statis; Mikšík, Ivan (Journal of chromatography. A, 2010)
Non-enzymatic posttranslational modifications of bovine serum albumin (BSA) by various oxo-compounds (glucose, ribose, glyoxal and glutardialdehyde) have been investigated using high-performance liquid chromatography (HPLC) and capillary zone electrophoresis (CZE). Both of these methods used mass spectrometric (MS) detection. Three enzymes (trypsin, pepsin, proteinase K) were used to digest glycated BSA. The extent of modification depended on the selected oxo-compound. Reactivity increased progressively from glucose to glutardialdehyde (glucose<ribose<glyoxal<glutardialdehyde). Carboxymethylation of lysine (CML) was the main type of modification detected. The HPLC/MS method achieved higher coverage and a larger amount of CML was identified compared to CZE/MS.
Keywords: elektroforéza kapilární; sérový albumin hovězí; Chromatography, High Pressure Liquid; Serum Albumin, Bovine; Animals; Cattle; Mass Spectrometry; hmotnostní spektrometrie; zvířata; vysokoúčinná kapalinová chromatografie; Protein Processing, Post-Translational; posttranslační úpravy proteinů; skot; Electrophoresis, Capillary